Mechanisms and models of pathogenesis of odontophobic reactions in children with different level of mental health - Dats, V. V.; Chugunov, V. V. (Journal of Education, Health and Sport, 2019)
The state of psychological well-being, and moreover, the state of mental health of the child has a significant impact on compliance with recommendations to ensure the optimal health of the oral cavity.The study of the effect of children's mental health on the health of their oral cavity is necessary for the further formation of highly congruent and personified recommendations for the care of teeth in each group of children with different levels of mental health. Despite the intense development of both pediatric psychiatry and pediatric dentistry, some aspects of it, including anxiety and phobia disorders in children with underlying mental health disorders, remain poorly understood.To understand approaches to the correction of the odontophobic reactions, a detailed study of the mechanisms of pathogenesis of such reactions is necessary to be completed.The purpose of the study: to form a typology and to describe pathogenesis of the odontophobic reactions in children with different levels of mental health, basing on the analysis of ethostomatological correlates.Contingents and methods. On the basis of Regional Clinical Dental Hospital, under the conditions of informed consent of parents and according to the principles of bioethics, 100 children with a variety of dental diseases with different levels of mental health, with odontophobic reactions were examined. They were divided into the following four groups: the first group consisted 30 patients with autism, the second group consisted 30 patients with oligophrenia of the mild degree, the third group consisted 20 patients with ADHD, the fourth group consisted mentally healthy children.Research results. Based on the comparative analysis of the clinical and semiotic content of the odontophobic reactions and the ethostomatological correlates in children with different levels of mental health, mechanisms of their pathogenesis have been established.In patients with autism, an insulating type of odontophobic reaction develops by statobehavioral pathogenetic mechanism, transaffective odontophobic reaction develops by disposition-reactive mechanism, and stenic-negativistic odontophobic reaction develops by hyperdefensive mechanism.In children with oligophrenia, confronational odontophobic reaction develops by hypoanalytical pathogenetic mechanism, vocalizational odontophobic reaction develops by situationally-determined mechanism, and agitational odontophobic reaction develops by pathocerebrotonic mechanism.In children with ADHD, motor odontophobic reaction develops by kinetodeprivational pathogenetic mechanism, partly-adherent odontophobic reaction develops by isomotivational mechanism, and explosive odontophobic reaction develops by transalgetic mechanism.In mentally healthy children, algophobic odontophobic reaction develops by algopreventative pathogenetic mechanism, transcompialant odontophobic reaction develops by hypomotivational mechanism, and escapational odontophobic reaction develops by distancing mechanism.